Dynamic changes of metabolic characteristics in neonatal intrahepatic cholestasis caused by citrin deficiency - Zhang, Ting; Zhu, Shasha; Miao, Haixia; Yang, Jianbin; Shi, Yezhen; Yue, Yuwei; Zhang, Yu; Yang, Rulai; Wu, Benqing; Huang, Xinwen (Frontiers in Molecular Biosciences, 2022)
Introduction: Neonatal intrahepatic cholestasis caused by citrin deficiency (NICCD) is a pan-ethnic complicated inborn error of metabolism but the specific mechanism is not fully understood. Methods: A total of 169 patients with NICCD which have biallelic pathogenic SLC25A13 variants detected by targeted next generation sequencing, were collected. They were divided into “Newborn-screen Group” and “Clinical diagnosed Group” depending on the newborn screening results. Amino acid and acyl carnitine profiles were measured by MS/MS. The total bile acids, blood amino acids and acyl carnitines, general biochemistry, blood count and coagulation parameters were monitored every 2 to 3 months. We compared the differences of metabolic indices and their dynamic changes between these two groups. SPSS 22.0 software and R 4.0.5 software were used for statistical analysis and boxplots drawing, respectively. Results: At the onset of NICCD, we found the “Clinical diagnosed Group” had higher levels of intermediate products of the urea cycle, free carnitine, short-chain and long-chain acylcarnitines than those in “Newborn-screen Group”, but the levels of ketogenic/glucogenic amino acids and several medium-chain acylcarnitines were lower. Furthermore, concentrations of direct bilirubin, total bile acid, lactate, prothrombin time and several liver enzymes were significantly higher in “Clinical diagnosed Group” while total protein, amylase and hemoglobin were lower. Dynamic change analysis showed the majority of characteristic metabolic indicators in “Newborn-screen Group” reached the peak concentrations at earlier ages as well as declined to normal levels. Sequential order analysis showed phenylalanine and tyrosine were the earliest abnormal amino acids in “Clinical diagnosed Group” while albumin was the earliest abnormal biochemical indicator in both groups. The coagulogram was early restored while citrulline, alpha fetoprotein and globulin were late recovered in both groups. c.852_855del (41.2%), IVS16ins3kb (17.6%), c.615+5G>A (9.6%), 1638_1660dup (4.4%) and c.1177+1G>A (3.7%) accounted for 76.5% of all the mutated SLC25A13 alleles in our population. The genotype-phenotype correlation was still not clear in citrin deficiency. Conclusion: The argininosuccinate synthesis, gluconeogenesis, ketogenesis, fatty acid oxidation, liver function and cholestasis were more severe affected in “Clinical diagnosed Group”. “Newborn-screen Group” had faster disease progression and better prognosis which highlighted the importance of newborn screening of NICCD.